IMAGES OF HISTORICAL FIGURES THROUGH THE PRISM OF PERCEPTION OF MYTHICAL REALITY - Madinabonu Akhmedova Makhmudjonovna (American Journals, 2024)
This article examines the images of historical personalities through the prism of perception of mythical reality. In Russian and Uzbek legends about historical figures, one bright personality always stands at the center of any event. These are legends with a clearly expressed historical basis, where the main plot unfolds around the legendary hero. In oral stories about famous people, passed from mouth to mouth, passing from generation to generation, the subject of transmission becomes their extraordinary deeds, actions, feats, outstanding merits that left an indelible mark in the people's memory, sometimes overgrown with an implausible story that embellishes reality. One of such characters in oral Russian folk legends is the image of Peter 1, and in Uzbek legends - the image of Amir Temur.
Keywords: Uzbek and Russian legends, historical figures, image, historical person, historical legends, phenomenon, mythological characters.